2012
DOI: 10.3758/s13421-012-0225-1
|View full text |Cite
|
Sign up to set email alerts
|

The strength-based mirror effect in subjective strength ratings: The evidence for differentiation can be produced without differentiation

Abstract: Criss (Cognitive Psychology 59:297-319, 2009) reported that subjective ratings of memory strength showed a mirror effect pattern in which strengthening the studied words increased ratings for targets and decreased ratings for lures. She interpreted the effect on lure items as evidence for differentiation, a process whereby lures produce a poorer match to strong than to weak memory traces. However, she also noted that participants might use different mappings between memory evidence and levels of the rating s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…Experimentally manipulating strength of encoding (e.g., by increasing study time; Ratcliff, Clark, & Shiffrin, 1990; Stretch & Wixted, 1998) not only increases hit rates, but also decreases the likelihood of false alarms to lures (i.e., a strength-based mirror effect; Glanzer & Adams, 1985). Whereas some accounts for this effect attribute it to response biases (Starns, White, & Ratcliff, 2012; Stretch & Wixted, 1998), it has been successfully modeled by assuming that the match signal aggregates evidence across the full set of targets, leading to a poorer match for lures when they are compared to more strongly encoded targets (Criss, 2010; Criss & McClelland, 2006; Kiliç, Criss, Malmberg, & Shiffrin, 2017; Shiffrin, Ratcliff, & Clark, 1990; Shiffrin & Steyvers, 1997). Our results provide converging evidence that the structure of encoded material can have profound effects that are specific to processes involved in probing memory (i.e., retrieval, rather than encoding, processes).…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally manipulating strength of encoding (e.g., by increasing study time; Ratcliff, Clark, & Shiffrin, 1990; Stretch & Wixted, 1998) not only increases hit rates, but also decreases the likelihood of false alarms to lures (i.e., a strength-based mirror effect; Glanzer & Adams, 1985). Whereas some accounts for this effect attribute it to response biases (Starns, White, & Ratcliff, 2012; Stretch & Wixted, 1998), it has been successfully modeled by assuming that the match signal aggregates evidence across the full set of targets, leading to a poorer match for lures when they are compared to more strongly encoded targets (Criss, 2010; Criss & McClelland, 2006; Kiliç, Criss, Malmberg, & Shiffrin, 2017; Shiffrin, Ratcliff, & Clark, 1990; Shiffrin & Steyvers, 1997). Our results provide converging evidence that the structure of encoded material can have profound effects that are specific to processes involved in probing memory (i.e., retrieval, rather than encoding, processes).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also attempted to test the unequal-variance assumption by directly calculating the variability of memory-strength ratings on scales that have many levels (e.g., 20 or 100 different rating options; Mickes, Wixted, & Wais, 2007; also see Criss, 2009, and Starns, White, & Ratcliff, 2012). As expected, studies of this sort show that ratings are more variable for targets than for lures.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, studies examined the effects of a particular manipulation on a subset of parameters only, and typically the manipulation consisted of two levels (e.g., fast vs. accurate SAT setting or easy vs. difficult condition) rather than the more detailed five levels used in the present study. Nevertheless, even with these caveats, previous studies found a number of deviations from the selective influence assumption such as speed emphasis leading to decreased non-decision times [40][41][42][43] , decreased drift rate variability 44 , and decreased drift rates 42,[44][45][46][47][48] . Moreover, easier stimuli were found to decrease the non-decision time, increase the starting point of the accumulation, and increase the decision boundary 41 .…”
Section: Selective Influence In the Diffusion Model The Diffusion Momentioning
confidence: 99%